Harmonisation et diffusion des ressources numériques 3D des grottes ornées - Violette Abergel; Geneviève Pinçon; Stéphane Konik; Kévin Jacquot (In Situ)
The national centre for prehistory (CNP, Centre national de la Préhistoire) serves as a depository for all the digital resources concerning prehistoric caves and shelters with parietal wall paintings. The centre tries to carry out a campaign of 3D digitisation every year in order to enrich its holdings. These resources are at one and the same time archival records of parietal painting and material for their future conservation, study and interpretation. Because they have not undergone any treatment or manipulation likely to bias their interpretation, this raw data represents for the centre and its partners a precious resource for documenting and studying prehistoric sites. So today it has become very important to better document and formalise these resources in order to guarantee their preservation and availability, both for the general public and for experts. Consequently, the centre has recently joined forces with the UMR MAP team, specialised in models and simulations for architecture and the heritage, in the framework of a general agreements between the Ministry of Culture and the CNRS and aiming at a better characterisation of the data so far acquired, and its better diffusion. The first point involves the production of pertinent descriptors in order to accompany the 3D data with clear cataloguing information about provenance, nature and quality. The second aspect of the project involves harmonising the data and ensuring its perpetuation and the development of prototype web platforms allowing for visualisation and manipulation via an adaptive interface. The project is part of a broader programme aimed at making a contribution to the traceability of 3D digital imagery produced for scientific research. In this article we propose a progress report on the work far carried out on digital data for parietal art, with particular focus on the recent developments in the visualisation of 3D data.